МАДАНИЯТЛАРАРО МУЛОҚОТ ТУШУНЧАСИНИНГ ТАЪРИФИ - Худайбергенов, А.А. (SCIENCE and SOCIETY, 2023)
In this article, analyzes were carried out on the basis of the principle of anthropocentrism, taking into account the "human factor" in the study of language in modern linguistics, and the definition of the concept of intercultural communication and the opinions of world linguists about the concept of intercultural communication.